Efecto de la Tintura de la Verbena (Verbena officinalis) para el tratamiento de Gingivitis en caninos domésticos (Canis lupus familiaris) - Analuisa Barriga, Fernanda Edelina (Ecuador : Latacunga: Universidad Técnica de Cotopaxi (UTC), 2021)
The present investigation project was a study to determine the Verbena tincture’s effect (Verbena officinalis) for the treatment of Gingivitis in Domestic Canines (Canis lupus familiaris), 20 canines were used at random from the Veterinary Clinic "My dog house" who subjected the animals to an application of Verbena Officinalis tincture in two treatments. The investigation method used was experimental, with signing techniques, laboratory and observation, using programs such as Infostat with a T-Student test and Excel to reflect the results. To assess its effectiveness, a clinical file was made for its follow-up, and a sample collection with a buccal swab on the gum, two research groups were developed, each one made up of 10 canines, the treatments were: T1 application of Tincture, twice a day every day for 30 days and T2, application of Tincture, passing one day, twice a day for 30 days, and new samples are taken to establish the bacterial CFU on days 15 and 30. The results obtained from the investigation had the following effectiveness percentages, for T1; gram positive bacterium like Staphylococcus aureus and Streptococcus spp got the 100 %, Bacillus spp with the 93.75%; Staphylococcus coagulasa negative, Streptoccocus beta hemolítico got the 93% , and for gram negative bacterium are: Pseudomonas spp 100%, Enterobacter cloacae, 89.17% and Escherichia Coli 60%. While the effectiveness percentages in T2 were: gram positives: Staphylococcus aureus and Streptococcus beta hemolítico with the 100%, Streptococcus spp 81.25%, Bacillus spp, 87.19%, Staphylococcus coagulasa negative, 59%, and gram-negative bacterium like: Pseudomonas spp y Escherichia Coli, 100%, y Enterobacter cloacae, 85%. Concluding that the Verbena Officinalis tincture has a concentration of 1785.79 mg of catechin, which has antioxidant properties. El presente proyecto de investigación fue un estudio para determinar el efecto de la tintura de Verbena (Verbena officinalis) para el tratamiento de Gingivitis en Caninos Domésticos (Canis lupus ...